The Revolution of Christian Religious Education in Indonesia: A Historical Liberation Perspective - Supit, Sugijanti (Peneliti.net, 2024)
This research aims to examine the history of Christian religious education in Indonesia, especially in the Protestant context, starting from the VOC era to the present, to assess its contribution such as liberating facilities for society, especially students. By examining the historical trajectory of Christian religious education in Indonesia, we can examine and make the necessary adjustments in its current implementation, especially in responding to the challenges of the ASEAN Economic Community (AEC) era. In order to achieve this goal, the literature method is a bridge that can be crossed using the correct procedures. The article produces an understanding of the importance of liberating Christian religious education after learning from its history in Indonesia. Through this discourse, it is hoped that we can identify and overcome our strengths and weaknesses in preparing students adequately to face the increasingly fierce competition of the contemporary era in the context of Christian religious education in Indonesia.